2013
DOI: 10.1083/jcb.2026oia90
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective intervention by interferon-γ blockade prevents CD8+ T cell-mediated dendrite and synapse loss

Abstract: Neurons are postmitotic and thus irreplaceable cells of the central nervous system (CNS). Accordingly, CNS inflammation with resulting neuronal damage can have devastating consequences. We investigated molecular mediators and structural consequences of CD8(+) T lymphocyte (CTL) attack on neurons in vivo. In a viral encephalitis model in mice, disease depended on CTL-derived interferon-(IFN-) and neuronal IFN-signaling. Downstream STAT1 phosphorylation and nuclear translocation in neurons were associated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 44 publications
0
44
0
1
Order By: Relevance
“…However other studies have demonstrated a pathogenic impact of IFNc in demyelinating disease [134,135], while still others saw no effect of IFNc deficiency on demyelination associated with an infection [136]. Further, there are clear indications that IFNc can exacerbate neuroinflammatory disease and drive neuronal loss in other settings [137].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 96%
“…However other studies have demonstrated a pathogenic impact of IFNc in demyelinating disease [134,135], while still others saw no effect of IFNc deficiency on demyelination associated with an infection [136]. Further, there are clear indications that IFNc can exacerbate neuroinflammatory disease and drive neuronal loss in other settings [137].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 96%
“…It was hypothesized that these microglia played an active role in the removal of these synapses, a process termed synaptic stripping. Synaptic stripping has been observed not only after axotomy or injury, but also following infection or inflammation (Di Liberto et al 2018;Kreutzfeldt et al 2013;Trapp et al 2007;Chen et al 2014), and it involves not only excitatory perisomatic synapses (like those on lower motoneurons; Blinzinger and Kreutzberg 1968) but also inhibitory perisomatic synapses (like those in neocortex and hippocampus; Di Liberto et al 2018;Chen et al 2014). While activation of microglia following insult and inflammation may lead to synaptic stripping, it does not in all cases (Siskova et al 2009;Perry and O'Conner 2010), nor is activation a requirement for microglial to phagocytose synaptic elements.…”
Section: Loss Of Perisomatic Synapses Coincides With Microglial Enshementioning
confidence: 99%
“…During LCMV meningitis, CD8 + T cells can induce a pathogenic recruitment of innate myelomonocytic cells that break down cerebral blood vessels and contribute to fatal CNS edema (Figure 1, Movie 2) [54]. CD8 + T cells can also release IFN-γ onto virally infected neurons, promoting loss of dendrites and synapses [55]. In contrast, another recent study showed that cerebral pathology does not always result from antiviral T cell activity in the infected CNS.…”
Section: Immune-mediated Control Of Cns Pathogensmentioning
confidence: 99%